Imaging the electrical activity of organelles in living cells - Ella Matamala (Nature Portfolio, 2021)
Matamala et al. adapt a hybrid-FRET voltage sensor to enable the recording of resting membrane potential of different organelle compartments in living cells. Their approach allows simple and precise subcellular targeting, the ability to record from individual organelles, and the potential for optical multiplexing of organellar activity.